A multidimensional version of the Carlson inequality - Bertolo, J. I. [UNESP]; Fernandez, D. L. (Elsevier, 1984)
We give a multidimensional extension of a one-dimensional integral inequality due to F. Carlson. The extension presented here involves Lp spaces with mixed norms in a very natural way. © 1984.
Keywords: MATHEMATICAL TECHNIQUES